12-Week Exercise Training, Independent of the Type of Exercise, Attenuates Endothelial Ischaemia-Reperfusion Injury in Heart Failure Patients - Thijssen, Dick H. J.; Benda, Nathalie M. M.; Kerstens, Thijs P.; Seeger, Joost P. H.; van Dijk, Arie P. J.; Hopman, Maria T. E. (Frontiers in Physiology, 2019)
Introduction. Reperfusion is required to salvage ischaemic tissue, but also causes further damage (i.e. ischaemia–reperfusion (IR)-injury). Heart failure patients reveal exaggerated IR-injury, whilst traditional ischaemic preconditioning cannot prevent IR-injury. Exercise training may be a more powerful preconditioning stimulus, especially high-intensity interval training (HIT) given the similarities with ischaemic preconditioning. Therefore, we examined the impact of 12-week continuous training (CT) versus HIT on brachial artery endothelial IR-injury in HF patients NYHA II-III. Methods. Twenty HF patients (male:female 19:1, 64±8 yrs, ejection fraction 38±6%) were allocated to 12-weeks of HIT (10*1-minute 90% maximal workload - 2.5-min 30% maximal workload) or CT (30-min 60-75% maximal workload). Before and after the intervention, we measured brachial artery endothelial function with flow-mediated dilation (FMD) before and after IR (5-min ischemic exercise, 15-min reperfusion). Results. IR caused a significant decline in FMD (CT (n=10): 5.2±2.5 to 3.4±1.6%, HIT (n=10): 5.3±2.6 to 3.5±1.6%, P=0.01), which was not different between groups (N.S.). Training improved maximal workload and fitness (P<0.05), with no differences between groups (N.S.). Exercise training did not alter FMD (N.S.), whilst IR did not impair FMD after exercise training (CT: 4.8±3.0 to 4.2±2.3%, HIT: 4.7±2.5 to 3.8±2.3%, N.S.). No changes were found in FMD before or after IR after 12-weeks in controls (n=9). Conclusion. We found that 12-week exercise training in HF patients mitigated endothelial ischaemia-reperfusion injury, an effect independent of the type of exercise. These changes may contribute to the cardioprotective effects of exercise training, whilst our findings highlight the potency of exercise as a preconditioning stimulus.